Pemanfaatan Ekstrak Kasar Daun Sirih Hijau (Piper betle) dan Daun Sirih Merah (Piper crocatum) Sebagai Antimikroba Pada Daging Ayam Broiler Segar - Parhusip, Adolf J.N.; Putridimara , Sabrina A.; Kristianto, Elin; Alfredo, Alfredo; Fraulencia, Jesseline (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Green betel plants (Piper betle) and red betel plants (Piper crocatum) are plants that found in many parts of Indonesia which can be categorized as medicinal plants. This is due to the content contained in green and red betel leaves which has phenolic compounds, such as flavonoids, tannins, and saponins. The research objective of this study was to utilize the extract of green betel leaf and red betel leaf by extracting ethanol FG 96% as an antimicrobial compound. There are 4 types of tested bacteria used in this study, they are Escherichia coli, Salmonella, S. aureus, and B. cereus. The extract concentrations used for the two types of leaf extract were 0, 5, 10, 15, and 20%. The sample used for TPC was a fresh broiler chickens, with immersion time for 0, 24, 48, and 72 hours. The total phenolic properties of the green and red betel leaf extracts were 2630.1 mg GAE/g and 6294.8 mg GAE/g, respectively. The total flavonoids possessed by the green and red betel leaf extract were 679.0 mg QE/g and 1662.9 mg QE/g, respectively. Both types of betel leaf extract can function as the best antimicrobial at a concentration of 20%. The bacteria that most resistant to green and red betel leaf extract is E. coli, and the bacteria that most sensitive to green and red betel leaf extract is S. aureus. The MIC and MBC values of Gram positive bacteria (S. aureus and B. cereus) were lower than the MIC and MBC values of Gram negative bacteria (E. coli and Salmonella). Key words: Green betel leaves; red betel leaves; extracts; fresh broiler chicken.